2020
DOI: 10.4143/crt.2019.249
|View full text |Cite
|
Sign up to set email alerts
|

Association of Body Composition with Long-Term Survival in Non-metastatic Rectal Cancer Patients

Abstract: Original ArticlePurpose We evaluated the association of body composition with long-term oncologic outcomes in non-metastatic rectal cancer patients. Materials and MethodsWe included 1,384 patients with stage(y)0-III rectal cancer treated at Asan Medical Center between January 2005 and December 2012. Body composition at diagnosis was measured using abdomino-pelvic computed tomography (CT). Sarcopenia, visceral obesity (VO), and sarcopenic obesity (SO) were defined using CT measured parameters such as skeletal m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
57
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 28 publications
(37 reference statements)
4
57
0
2
Order By: Relevance
“…Sarcopenia has been reported to affect survival in various kinds of malignancies, including colorectal cancer [ 8 , 10 , 13 , 14 , 15 ]; however, criteria and measurement of sarcopenia were inconsistent among studies [ 13 , 14 , 16 ]. In most previous studies, the associations between sarcopenia and survival were evaluated for a single timepoint [ 14 , 15 , 16 ]. Although the mechanism through which sarcopenia influences prognosis in patients with cancer is unknown, there is a hypothesis that sarcopenia induces systemic inflammation [ 2 , 14 ], which is also known to increase the risk of cancer and diminish treatment efficacy [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sarcopenia has been reported to affect survival in various kinds of malignancies, including colorectal cancer [ 8 , 10 , 13 , 14 , 15 ]; however, criteria and measurement of sarcopenia were inconsistent among studies [ 13 , 14 , 16 ]. In most previous studies, the associations between sarcopenia and survival were evaluated for a single timepoint [ 14 , 15 , 16 ]. Although the mechanism through which sarcopenia influences prognosis in patients with cancer is unknown, there is a hypothesis that sarcopenia induces systemic inflammation [ 2 , 14 ], which is also known to increase the risk of cancer and diminish treatment efficacy [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that body composition affected the long-term survival of patients with non-metastatic rectal cancer [ 15 ]; rectal cancer patients with sarcopenic obesity and a low BMI at diagnosis had a negative association with OS. Although we showed that body composition was associated with OS, it could not reflect postoperative changes in body composition.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, lower physical function, decreased resilience to chemotherapy and radiation treatment, and generally worse prognoses are observed in cachectic patients compared to those with stable weight [6]. However, other body composition parameters including muscle quantity and density have recently become a subject of research in the field of cancer prognosis [7].…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Many studies only measure baseline/single time point of body compositions to diagnose patients with sarcopenia, sarcopenic obesity or visceral obesity, which sometimes influence but usually do not affect oncological outcomes. 8,14,15,16 Of note, over time, more and more studies have paid more attention to the relationship between changes in body composition and clinical outcomes in cancer patients. Measuring body composition changes over time is necessary to obtain more information about patients.…”
Section: Introductionmentioning
confidence: 99%